PENGARUH PENAMBAHAN ARANG DAN CUKA KAYU TERHADAP PERTUMBUHAN ANAKANShorea platyclados Sloot ex Fowx DAN Shorea selanica Blume - Sri Komarayati; Heru S. Wibisono (Jurnal Penelitian Hasil Hutan, 2016)
Charcoal and wood vinegar are organic matters that can be used for soil improvement and induce plant growth. This paper studies the effect of charcoal and wood vinegar treatments into Shorea platyclados and Shorea selanica seedling's growth. The seedling growth parameters measured include seddling height and diameter, based on charcoal and wood vinegar treatments. Results show combination of 10% charcoal and 1% wood vinegar grows the highest seedling height average of 47.77cm and 1% wood vinegar treatment grew seedling's diameter average up to 6.23 cm of Shorea platyclados. The greatest average of Shorea selanica seedling's diameter of 5.28 cm was achieved by treatment of 10% charcoal and 1% wood vinegar.